2017
DOI: 10.1021/acs.chemmater.7b00931
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Fade in Solid-State Batteries: Interphase Formation and Chemomechanical Processes in Nickel-Rich Layered Oxide Cathodes and Lithium Thiophosphate Solid Electrolytes

Abstract: All-solid-state lithium ion batteries may become long-term, stable, high-performance energy storage systems for the next generation of electric vehicles and consumer electronics, depending on the compatibility of electrode materials and suitable solid electrolytes. Nickel-rich layered oxides are nowadays the benchmark cathode materials for conventional lithium ion batteries because of their high storage capacity and the resulting high energy density, and their use in solid-state systems is the next necessary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
892
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 765 publications
(955 citation statements)
references
References 49 publications
22
892
3
Order By: Relevance
“…Additionally, state-of-the-art CAMs undergo significant volume changes during lithium (de) intercalation (Figure 2c), [35,36] which often leads to detrimental contact loss within the composite cathode ( Figure 2d). [27] It will therefore be of interest to explore whether coatings can mechanically confine CAMs in order to reduce such volume changes, which may mitigate crack formation as well, or perhaps enhance adhesion within the cathode composite in order to prevent contact losses. [37] Furthermore, given that uncoated NCM materials are known to evolve oxygen during cycling, [38,39] even in an SSB environment, an interesting additional question will be whether coatings can chemically stabilize NCM-type active materials at high potentials to also inhibit gas evolution.…”
Section: Cam Coatings For Ssbs: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, state-of-the-art CAMs undergo significant volume changes during lithium (de) intercalation (Figure 2c), [35,36] which often leads to detrimental contact loss within the composite cathode ( Figure 2d). [27] It will therefore be of interest to explore whether coatings can mechanically confine CAMs in order to reduce such volume changes, which may mitigate crack formation as well, or perhaps enhance adhesion within the cathode composite in order to prevent contact losses. [37] Furthermore, given that uncoated NCM materials are known to evolve oxygen during cycling, [38,39] even in an SSB environment, an interesting additional question will be whether coatings can chemically stabilize NCM-type active materials at high potentials to also inhibit gas evolution.…”
Section: Cam Coatings For Ssbs: General Considerationsmentioning
confidence: 99%
“…[19,20] Unfortunately, thiophosphates also have a rather narrow electrochemical stability window, i.e., the onset of oxidative decomposition begins even before 3 V versus Li + /Li due to S(0)/S(−2) redox reactions, while reductive decomposition is theoretically expected at potentials of about 1.7 V versus Li + /Li due to P(+5)/P(−3) redox reactions. [2,[26][27][28] Several years ago, Takada summarized the early work on SSBs and described the need for coatings against the formation of space charge layers at the interface between high-voltage cathodes and thiophosphate SEs. The perfect SE would combine the ionic transport properties of thiophosphates, the mechanical properties of polymers, and the oxidation stability of oxides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[243] Contrary to rigid oxide SSEs, soft sulfide SSEs easily form a close contact with cathode materials by applying pressure, thereby avoiding annealing-induced elemental interdiffusion. materials upon delithiation, [247] as demonstrated in Figure 13e. A. Sakuda et al [244] employed the TEM technique to find that Co, P and S diffused mutually at the LiCoO 2 /Li 2 S-P 2 S 5 interface during the first battery charging, forming a resistive interfacial layer (Figure 13d).…”
Section: Origin Of the Interfacial Resistancementioning
confidence: 90%
“…[241] The depth-resolved X-ray absorption spectroscopy measurement coupled with TEM analysis also indicated that some inactive Co 3 O 4 (Figure 13c) was produced at the LiCoO 2 /LATP interface by charging the ASSLIBs, reducing the number of active sites for Li + migration across the interface. [247] Copyright 2017, American Chemical Society. [243] Contrary to rigid oxide SSEs, soft sulfide SSEs easily form a close contact with cathode materials by applying pressure, thereby avoiding annealing-induced elemental interdiffusion.…”
Section: Origin Of the Interfacial Resistancementioning
confidence: 99%